Personalities Factors Toward Engineering Entrepreneurial Attitudes - Ong, Wei Heng (2020)
Nowadays, entrepreneurship is the major factor that can drive the world economic growth and create more jobs opportunity in order to reduce the unemployment rate. A healthy and good society can only emerge when countless entrepreneurial activities are carried out continuously. As a developing country, Malaysia is focusing on entrepreneurship to restore and stabilize its economy. There are undeniable benefits to be an entrepreneur in Malaysia. One of the benefits of doing so is that it can cope with Malaysia’s rising unemployment rate and bring job opportunities to fresh graduates especially the engineering students. Therefore, entrepreneurial attitude among engineering students in public and private universities will be the title in this study. Past literature has reported that a person’s entrepreneurial attitudes determines whether he or she can successfully set up a new company and participate in business activities. Specific personality traits enable individuals to act like entrepreneurs and conduct entrepreneurial activities which including but not limited to locus of control, risktaking and need for achievement. Therefore, this study aims to investigate the personality factors toward entrepreneurial attitude among engineering students in public and private higher education institution. This study was conducted based on three public and three private universities in Malaysia. The research data were collected by questionnaire survey and the results shows the engineering students with entrepreneurial attitude in public universities are more toward need for achievement traits while the engineering students in private universities are more toward locus of control traits.